Limited effect of red blood cell transfusion on long-term mortality among anaemic cardiac surgery patients. (28th July 2020) - Tran, Long; Greiff, Guri; Wahba, Alexander; Pleym, Hilde; Videm, Vibeke
Abstract: OBJECTIVES: Our goal was to investigate long-term mortality associated with red blood cell (RBC) transfusion among patients with anaemia undergoing cardiac surgery when adjusting for known risk factors. METHODS: Adults with preoperative anaemia as defined by World Health Organization criteria undergoing open-heart surgery from 2000 through 2017 were included. Cox regression was performed for long-term mortality (30 days–5 years), comparing patients who received ≥1 unit of RBC with those who did not. Unadjusted and multivariable analyses adjusted for risk factors were performed. RESULTS: The study included 1859 patients, 1525 (82%) of whom received RBC transfusion. A total of 370 (19.9%) deaths were registered between 30 days and 5 years; 88 patients (23.8%) died between 30 days and 1 year. The unadjusted hazard ratio (HR) associated with RBC transfusion was 2.09 (1.49–2.93, P  <   0.001) from 30 days to 5 years postoperatively. The HR for RBC transfusion were 4.70 (1.72–12.81, P  =   0.002) and 1.77 (1.23–2.55, P  =   0.002) for 30 days–1 year and 1–5 years, respectively. Adjusting for perioperative risk factors, which included postoperative complications, the HR decreased to 1.16 (0.80–1.68, P  =   0.43), 1.79 (0.63–5.12, P  =   0.28) and 1.11 (0.75–1.65, P  =   0.61) for observation time from 30 days to 5 years, 30 days to 1 year and 1 to 5 years, respectively. Results were similar when postoperative complications were excluded from the adjustment variables. CONCLUSIONS: No statistically significant association between RBC transfusion and long-term mortality was found when we adjusted for known risk factors. This study suggests that the observed difference in mortality in this patient group is largely due to patient-related risk factors.